(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Securing tenure rights to land is recognized as an indicator to achieve the sustainable development goals as outlined in Agenda 2030. Land is an essential foundation for vulnerable indigenous peoples to maintain their livelihood and identity. By providing a case study of the Orang Asli Temuan in Negeri Sembilan on the customs, practices, use and traditions relating to land, drawn on the framework of common law jurisprudence on indigenous peoples’ customary land, this paper illustrates the significance of land and its security for the communities. In particular, by using case study, this paper investigates the customary land of the Orang Asli in selected villages: Langkap in Kuala Pilah, Parit Gong in Jelebu and Bukit Kepong in Pasir Panjang. It is found that the Temuan Orang Asli regard the land and territory that they live in as belonging to their own community, and its maintenance based on Adat Perpatih is vital for the community and future generations. Within this territory, there are areas surrounding the settlement and agricultural areas that they regard as foraging areas which function as a buffer zone for community members. It is evident that the Orang Asli communities have their own "legal system" based on their customs and community system. The research findings are important to provide knowledge and understanding of the communities and their practices, which may pave the way towards changes in laws and policies to better protect these peoples, consistent with sustainable development goals. Keywords: Orang asli, Temuan, customary land, adat perpatih, Sustainable Development Goals (SDGs)